Novel 1,1'-bisisoquinolines : synthesis, resolution and application in asymmetric catalysis - Gao, Qi (2010)
This thesis deals with the chemistry of novel 1,1'-bisisoquinolines and derivatives. Application of enantiopure 1,1'-bisisoquinolines as ligands for various asymmetric C-C bond forming reactions has been examined. Condition for the preparation of the anticipated 1,1'-bisisoquinolines has been established. Racemic C2-symmetric 1,1'-bisisoquinolines and pseudo symmetric 1,1'-bisisoquinolines were synthesized through classical double Bischler-Napieralski reaction followed by reduction with borohydrides. Racemic pseudo symmetric 1,1'-bisisoquinoline could also be synthesized directly through double Bischler-Napieralski reaction using polyphosphoric acid at elevated temperatures. Resolution of the racemic 1,1'-bisisoquinolines via diastereomeric salt and covalent bond formation was explored thoroughly. Diasteromeric salts failed to separate to give individual enantiomers. Covalent bond formation using chiral isocyanates such as α-methylbenzyl isocyanate gave diastereomeric urea derivatives that were separated by a combination of column chromatography and recrystallization techniques. Acid and base catalyzed alcoholysis approaches were explored to obtain the free enantiopure 1,1'-bisisoquinolines. Difficulties were met during the alcoholysis mainly due to racemization of the enantiomers. However, after optimization of the reaction conditions, base alcoholysis followed by recrystallization gave the required 1,1'-bisisoquinoline in enantiopure form. The reactivity and structural features of (+)-1,2,3,4-tetrahydro- -1,1'-bisisoquinoline were explored in details through formation of various N-alkyl, amide, urea and thiourea derivatives and by studying the X-ray structures of some of these derivatives.